Design Architecture of Jembrana E-government System - Kainde, Henry Valentino Florensius; Anggara Wijaya, I Nyoman Yudi (Universitas Sam Ratulangi, 2020)
Abstract — E-government (e-gov) is the use of information technology that can improve the relationship between the government and other parties. The use of information technology then produces new forms of relationships such as: G2C (Government to Citizen), G2B (Government to Business Enterprises), and G2G (inter-agency relationship). The Jembrana regional government has an area of 841.80 km2, five districts and fifty-one sub-district, has difficulty in collecting data, especially population data. For that we need an information system that can integrate districts and sub-districts with local governments. So that, the population data at the sub-district level will be easily obtained by the Jembrana regional government. Keywords — e-gov, information technology, planning, government Abstrak — E-government (e-gov) adalah penggunaan teknologi informasi yang dapat meningkatkan hubungan antara pemerintah dengan pihak-pihak lain. Penggunaan teknologi informasi ini kemudian menghasilkan hubungan bentuk baru seperti: G2C (Government to Citizen), G2B (Government to Business Enterprises), dan G2G (inter-agency relationship). Pemerintah daerah jembrana yang memiliki luas wialayah 841,80 km2 dan memiliki lima kecamatan dan lima puluh satu kelurahan kesulitan dalam melakukan pengumpulan data, terutama data penduduk. Untuk itu diperlukan suatu sistem informasi yang dapat meintegrasikan kelurahan dengan kecamatan dan kecamatan dengan pemerintah daerah. Sehingga nantinya data penduduk pada tinggkat kelurahan akan mudah didapat oleh pemerintah daerah jembrana. penelitian telah menghasilkan suatu perancangan system yang berorientasi objek dari fungsionalitas perangkat lunak, use case diagram, class diagram, ERD sistem, konseptual database dan perancangan interface sistem.Kata Kunci : e-gov, teknologi informasi, rencana, pemerintah